Kajian Etnosains Tradisi Bunuk Masyarakat Desa Loli, Kabupaten Timor Tengah Selatan Sebagai Sumber Belajar Biologi - Theodora Sarlotha Nirmala Manu; Yanti Daud; Eritrika Adriana Nulik (Postgraduate, University of Mataram, 2026)
The integration of local wisdom into biology learning remains limited, even though ethnoscience has strong potential to provide contextual and meaningful learning experiences for students. One form of local wisdom found in South Central Timor Regency is the bunuk tradition practiced by the community of Loli Village. This study aimed to analyze the potential of the bunuk tradition as a biology learning resource for senior high school students. This study employed a descriptive qualitative approach involving community members who inherit and practice the bunuk tradition. Data were collected through interviews, observations, and documentation, and were analyzed using data triangulation techniques. The results showed that the bunuk tradition contains ethnoscientific values related to environmental conservation, ecosystem balance, and interactions among living organisms within ecosystems. The feasibility assessment conducted by biology teachers indicated that the bunuk tradition met the criteria of being economical, practical, flexible, and aligned with the objectives of biology learning. The findings suggest that the bunuk tradition can function as a contextual biology learning resource that supports meaningful learning while preserving local cultural values. This study contributes to the development of ethnoscience-based biology learning and provides a reference for integrating local wisdom into science education.